Conjugated porous Polymers as Highly Efficient Heterogeneous Visible Light Photocatalyst. Issue 1784 (4th June 2015) - Wang, Zi Jun; Landfester, Katharina; Zhang, Kai A. I.
ABSTRACT: Π-conjugated porous polymers with hierarchical pore structures were synthesized via high internal phase emulsion polymerization (polyHIPE) technique. The polymers could be used as heterogeneous photocatalysts for highly selective oxidation of organic sulfides into sulfoxides and the free radical polymerization of methyl methacrylate (MMA) under visible light irradiation.